Moodle and BigBlueButton: A proposal for educational material for distance courses at the Federal Institute of Education of Maranhão (IFMA) (Research, Society and Development, 2023)
The integration of Moodle and BigBlueButton is a proposal for didactic material for distance learning courses at IFMA. These tools combine to provide a complete and interactive online learning environment. The objective of this study was to highlight the advantages of integrating Moodle and BigBlueButton, providing a proposal for didactic material for distance learning courses at IFMA. The methodology adopted consisted of a literature review on Moodle, BigBlueButton and the integration of these tools. Studies, experience reports and best practices were analyzed to support the proposed didactic material. The integration of Moodle and BigBlueButton offers significant benefits for IFMA distance learning courses. It combines the organizational and interactive structure of Moodle with the videoconferencing and real-time collaboration capabilities of BigBlueButton. This integration provides flexibility, interaction, centralization of educational activities and access to varied educational resources. It is critical to empower teachers to use these tools effectively and promote engaging and efficient online learning experiences for students.